2021
DOI: 10.1016/j.clinimag.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Review of COVID-19, part 2: Musculoskeletal and neuroimaging manifestations including vascular involvement of the aorta and extremities

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) has affected almost every country in the world resulting in severe morbidity, mortality and economic hardship, altering the landscape of healthcare forever. Its devastating and most frequent thoracic and cardiac manifestations have been well reported since the start of the pandemic. Its extra-thoracic manifestations are myriad and understanding them is critical in diagnosis and diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 95 publications
0
5
0
4
Order By: Relevance
“…Accumulating evidences have showed that the musculoskeletal symptoms can occur during the first days of infection, even before the common respiratory symptomatology (dry cough, nasal congestion, sore throat and dyspnoea). Fatigue, arthralgia (joint pain), myalgia (muscle pain) and muscle weakness have been reported as initial and common symptoms by COVID-19-positive individuals ( Figure 3 ) ( Baj et al, 2020 ; Chan et al, 2020 ; Cipollaro et al, 2020 ; Ali and Kunugi, 2021 ; Kanmaniraja et al, 2021 ; Knight et al, 2021 ). Unfortunately, these extenuating symptoms can decrease the individuals’ ability to perform activities of daily living (ADL) such as ambulating, dressing, housecleaning and working ( Edemekong et al, 2021 ), which reduces the quality of life, generating anxiety and depression.…”
Section: The Musculoskeletal Symptomatologymentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidences have showed that the musculoskeletal symptoms can occur during the first days of infection, even before the common respiratory symptomatology (dry cough, nasal congestion, sore throat and dyspnoea). Fatigue, arthralgia (joint pain), myalgia (muscle pain) and muscle weakness have been reported as initial and common symptoms by COVID-19-positive individuals ( Figure 3 ) ( Baj et al, 2020 ; Chan et al, 2020 ; Cipollaro et al, 2020 ; Ali and Kunugi, 2021 ; Kanmaniraja et al, 2021 ; Knight et al, 2021 ). Unfortunately, these extenuating symptoms can decrease the individuals’ ability to perform activities of daily living (ADL) such as ambulating, dressing, housecleaning and working ( Edemekong et al, 2021 ), which reduces the quality of life, generating anxiety and depression.…”
Section: The Musculoskeletal Symptomatologymentioning
confidence: 99%
“…These systematic and meta-analysis studies summarize evidences on extrapulmonary features of the infection, aiming to contribute to a better diagnosis, prevention and treatment of COVID-19. Generally, they cited the prevalent muscle symptoms reported by hospitalized patients during the acute phase of SARS-CoV-2 infection ( Abdullahi et al, 2020 ; Ashraf et al, 2020 ; Small and Beatty, 2020 ; Zaim et al, 2020 ; Disser et al, 2020 ; do Nascimento et al, 2020 ; Ghayda et al, 2020 ; Gupta et al, 2020 ; Kordzadeh-Kermani et al, 2020 ; White-Dzuro et al, 2021 ; Kanmaniraja et al, 2021 ; Ramani et al, 2021 ; Ramos-Casals et al, 2021 ), which highlights once more the biased towards severe cases of COVID-19.…”
Section: The Lack Of Musculoskeletal Data Related To Mild To Moderate...mentioning
confidence: 99%
“…Вследствие полиорганной недостаточности, сепсиса, гипергликемии, искусственной вентиляции легких и парентерального питания развиваются электролитные и метаболические изменения, которые также могут способствовать так называемой миопатии и полинейропатии критического состояния [13]. Локальная боль в мышцах может быть следствием внутримышечных гематом, которые возникают в связи с применением антикоагулянтов для профилактики и лечения тромбоэмболических осложнений при COVID-19 [23]. Гематомы проявляются в виде пальпируемых образований, часто сопровождающихся болью и экхимозами; может отмечаться снижение гематокрита.…”
Section: механизмы артралгии и миалгии при коронавирусной инфекцииunclassified
“…Иногда внутримышечные гематомы вызывают неврологические симптомы в результате сдавления соседних сосудисто-нервных структур [24]. В последующем может развиваться атрофия пораженной мышцы с развитием жировой инфильтрации и кальцификации [23].…”
Section: механизмы артралгии и миалгии при коронавирусной инфекцииunclassified
See 1 more Smart Citation